Exercise-induced methylation of the Serhl2 promoter and implication for lipid metabolism in rat skeletal muscle - Mutsumi Katayama; Kazuhiro Nomura; Jonathan M. Mudry; Alexander V. Chibalin; Anna Krook; Juleen R. Zierath (Molecular Metabolism)
Objectives: Environmental factors such as physical activity induce epigenetic modifications, with exercise-responsive DNA methylation changes occurring in skeletal muscle. To determine the skeletal muscle DNA methylation signature of endurance swim training, we used whole-genome methylated DNA immunoprecipitation (MeDIP) sequencing. Methods: We utilized endurance-trained rats, cultured L6 myotubes, and human skeletal muscle cells, employing MeDIP sequencing, gene silencing, and palmitate oxidation assays. Additional methods included promoter luciferase assays, fluorescence microscopy, and RNA/DNA analysis to investigate exercise-induced molecular changes. Results: Gene set enrichment analysis (GSEA) of differentially methylated promoter regions identified an enrichment of four gene sets, including those linked to lipid metabolic processes, with hypermethylated or hypomethylated promoter regions in skeletal muscle of exercise-trained rats. Bisulfite sequencing confirmed hypomethylation of CpGs in the Serhl2 (Serine Hydrolase Like 2) transcription start site in exercise-trained rats. Serhl2 gene expression was upregulated in both exercise-trained rats and an ''exercise-in-a-dish'' model of L6 myotubes subjected to electrical pulse stimulation (EPS). Serhl2 promoter activity was regulated by methylation and EPS. A Nr4a binding motif in the Serhl2 promoter, when deleted, reduced promoter activity and sensitivity to methylation in L6 myotubes. Silencing Serhl2 in L6 myotubes reduced intracellular lipid oxidation and triacylglycerol synthesis in response to EPS. Conclusions: Exercise-training enhances intracellular lipid metabolism and phenotypic changes in skeletal muscle through epigenomic modifications on Serhl2. Hypomethylation of the Serhl2 promoter influences Nr4a transcription factor binding, promoter activity, and gene expression, linking exercise-induced epigenomic regulation of Serhl2 to lipid oxidation and triacylglycerol synthesis.